Experimental Investigation and mathematical modeling of the thermal shrinkage of bovine pericardium - Dück, Johann; Marashdeh, Mohannad; Breiter, Roman (Journal of Medical and Biological Engineering, 2011)
A model has been developed in the current study, which relates the extent of shrinkage to the progress of collagen denaturation. The model includes the cases of shrinkage of the samples of the pericardium under isothermal conditions and the case of shrinkage under constant load and heating. The kinetic parameters, determined from the isothermal shrinkage experiments, are the activation energy, E = 565.95 kJ/mol and the frequency factor, A = 8.64 × 10 sec . The current model fits the isothermal and the non-isothermal cases satisfactorily. A limitation of the model is its inability to describe the initial slow region at low temperatures. It cannot be modeled or fitted well because the model describes the progress of the shrinkage as one single exponential step.
Keywords: Modeling; Pericardium; Progressive denaturation; Thermal shrinkage

On the Conditions of Clogging in a Hydrocyclone - Dück, Johann; Minkov, L. L. (Theoretical Foundations of Chemical Engineering, 2019)
Abstract: Experimental data on the flow boundaries of a barite suspension depending on its concentration and volume flow rate for a 10 mm high-pressure hydrocyclone were presented. Computer simulation of phase separation in the high-pressure hydrocyclone was performed for a concentrated suspension. Qualitative agreement between the results of numerical modeling and experiment on the conditions of clogging of the hydrocyclone underflow was obtained.
CRIS-Team Scopus Importer:2019-09-17
Keywords: concentrated suspension; experiment; hydrocyclone clogging; numerical modeling

Optimizing the separation characteristics of the waterinjection hydrocyclone using mathematical modelling - Minkov, Leonid; Dück, Johann; Hassan, Mohamed M. A.; Ali, Mahrous A. M.; Farghaly, Mohamed G. (Mining of Mineral Deposits, 2021)
Purpose. Although the hydrocyclone separator has many advantages, it still has some limitations which decrease its separation efficiency in many mineral processing applications because of fine particles which are miss separated to the coarse product in the underflow. Water injection in the conical part of the cyclone was recently implemented to solve this problem. The water injection mechanism and the way in which the injected water affects the separation are still not clear and need to be more investigated.
CRIS-Team WoS Importer:2022-01-14